Neurobehavioural and Analgesic Properties of Ethanol Bark Extract of Terminalia ivorensis A Chev. (Combrataceae) in Mice - Adeoluwa, O. A.; Aderibigbe, A. O.; Agu, G. O.; Adewole, F. A.; Eduviere, A. T. (Drug Research, 2015)
Background:Terminalia ivorensis A. Chev (Combretaceae) is a medicinal plant used in folk medicine in the management of pain, rheumatic condition, gastroenteritis and as a tranquilizer in psychotic disorder.Objective: We evaluated neurobehavioural and analgesic properties of the ethanol bark extract of T. ivorensis (EBETI).Materials and methods: Effects of EBETI (1.25, 2.5, and 5 mg/kg) on novelty-induced behaviours were determined using open field test. Anxiolytic effect of EBETI (1.25, 2.5, and 5 mg/kg) was assessed using hole-board and elevated-plus maze paradigms. Analgesic property of EBETI (2.5, 5, and 10 mg/kg) was evaluated using acetic acid induced writhing, formalin and tail immersion tests. The extract was administered once intraperitoneally.Results: The LD50 of EBETI was 173 mg/kg. EBETI (1.25, 2.5, and 5 mg/kg) significantly reduced rearing (142.3±1.6, 83.5±1.9, 39.3±1.5) and grooming (33.8±3.4, 28.4±3.0, 18.2±1.7) as compared with controls (180.5±4.9; 52.4±5.2). Treatment with EBETI (1.25, 2.5, and 5 mg/kg) significantly reduced head-dipping on hole-board (9.4±2.3, 6.2±1.9, 5.4±2.9) as compared with control (26.8±1.9). However, there was no anxiolytic effect on EPM. EBETI (2.5, 5, and 10 mg/kg) significantly inhibited abdominal constriction in writhing assay (21.8.0±2.4, 12.2±1.6, 5.8±2.1) as compared with control (35.0±1.7). Inhibition of neurogenic and inflammatory phases of formalin test was notice. However, the extract could not alter response to thermal stimulus in tail immersion test.Discussion and conclusion: EBETI is sedative and has analgesic effect, thus supporting its folkloric use in pain management and as a tranquilizer in psychosis.
Keywords: analgesic; neurobehaviour; Terminalia ivorensis; tranquilizer